Micro-Controller Based Biogas Production Monitoring System - Junus, Mochammad; Dhea Rahman, Akbar; Fikri Shodiq, Ridhofir (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
Biogas still has limitations in monitoring gas quality parameters and mobility. This research aims to design an IoT-based mini biogas reactor equipped with a contaminant purification system, wheels for mobility, and a solenoid valve for automatic gas flow and integrated sensors to optimize biogas production and safety. The prototype is designed by integrating MQ-4 (CH₄), MQ-135 (CO₂), MPX5700AP (pressure), and DS18B20 (temperature) sensors connected to an Arduino nano. Sensor data is processed in real-time and displayed on a 20x4 LCD, while a SIM800L GSM module sends data via SMS periodically. The stepwise purification system using activated carbon successfully increased the purity of CH₄ from 55% to >70%. This research proves that IoT integration, automatic purification can be an innovative solution to improve production efficiency, safety, in rural and livestock environments. Keywords: Biogas, IoT, Arduino, Gas Purification Gas, Sensor Gas, Real Time.